Advances in heterocyclic chemistry. - Katritzky, Alan R. (Advances in heterocyclic chemistry, 1994)
Established in 1960, Advances in Heterocyclic Chemistry is the definitive serial in the area-one of great importance to organic chemists, polymer chemists, and most biological scientists. Every fifth volume ofAdvances in Heterocyclic Chemistry contains a cumulative subject index.